Resistência de Fimbristylis miliacea (L.) Vahl aos herbicidas inibidores da enzima ALS - Schaedler, Carlos Eduardo (2011)
Rice is one of the main foods for the most part of the world population. One of the main barriers that limit the full expression of the potential productivity of this crop is the competition by weeds. Among the methods of weed control in rice fields, herbicide is the most used. However, the evolution of many cases of resistance to these chemicals for several weed species has required farmers to adopt alternative methods of control and / or alternate herbicide mechanisms of action, which does not always result in the desired efficiency. The objective of this study was to explore the resistance of Fimbristylis miliacea biotypes to ALS inhibitor herbicides. Four studies were conducted: one in the field, two in greenhouse and one in the laboratory. It was determined the cross-resistance to ALS-inhibiting herbicides in field conditions (Article 1); caracterized the resistance level dose-response curve experiments were conducted in the greenhouse with two resistant biotypes (FIMM 10 FIMMI 12) and one susceptible (FIMM 13) (Article 2); it was compared the competitive ability and competition for light and nutrients resources between the biotypes of F. miliacea resistant and susceptible to ALS-inhibiting herbicides, and these with rice (Article 3); and it was sequenced the ALS enzyme gene from the biotypes studied to evaluate the mechanism of resistance to ALS-inhibiting herbicides (Article 4). The study 1 (Article 1) was conducted in Santa Catarina in a flooded rice field with resistant populations to pyrazosulfuron-ethyl. The study 2 (Article 2) and a part of the research of study 3 (article 3) were conducted in a greenhouse at the Departament of Plant Protection ( Fitossanidade ), UFPel in Capão do Leão RS; part of the research of study 3 (Article 3) and study 4 (Article 4) was conducted in the Department of Crop, Soil and Environmental Sciences at the University of Arkansas - Fayetteville, AR, USA. In field conditions, it was determined that F. miliacea is cross-resistant to ALSinhibitors herbicides. The biotype FIMMI 10 showed cross-resistance to three chemical families of ALS-inhibiting herbicides (pyrimidinylthiobenzoates, sulfonylureas and triazolopyrimidines). FIMMI 12 biotype showed cross resistance to two ALS-inhibiting herbicides (sulfonylureas and triazolopyrimidines). In equal proportions of plants, the rice, regardless of FIMMI biotype, presented, in general, higher values in the variables evaluated. Intraspecific competition is stronger among rice plants than interspecific with FIMMI biotypes. The competition for soil resources had higher effect for F. miliaceae and rice. Analysis of the nucleotide and amino acid sequences among the different biotypes indicated that a single point mutation, Thymine-Adenine, in the FIMMI 10 biotype; the mutation found resulted in an amino acid substitution Asp376Glu, in the region F between C, A, D and B, E domains of the ALS gen.